Psikologi Remaja Muslim - Elfi Yuliani Rochmah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2017)
Abstract: Teenagers are individuals who have reached puberty that is where he has reached the age of 15 years in chronological order and are already having a wet dream or not, so that the laws can be applied to him as an adult. Psychologically, adolescents are divided into two periods: early and late teens. Where the early teens is for those who chronologically was in junior high school ( age 12/13 years to 16 years ) and adolescents generally end in high school ( 17 years to 21 years ). In the phase of puberty adolescence are divided into pre-pubescent and post-pubescent followed generally entered adolescence where developmental aspects foreshadowed in adolescent development. To give an example of how you should behave and Islamic youth activities, can be extracted from the stories of the Prophets and Apostles and Companions .Keywords: Puberty, Adolescence Prophets, and developmental psychology approach